The Prevalence of Glaucoma in the Jirel Ethnic Group of Nepal - Miller, Sarah; Blackburn, Nicholas B.; Johnson, Matthew; Laston, Sandra; Subedi, Janardan; Charlesworth, Jac C.; Blangero, John; Towne, Bradford; Thapa, Suman S.; Williams-Blangero, Sarah (Frontiers in Ophthalmology, 2022)
Glaucoma is one of the leading causes of blindness worldwide with individuals in Asia disproportionately affected. Using a cross-sectional study design as part of the Jiri Eye Study, we assessed the prevalence of glaucoma in the Jirel population of Nepal and provide new information on the occurrence of glaucoma in south central Asia. Over a four-year period, 2,042 members of the Jirel population, aged 18 years and older, underwent a detailed ocular examination. Glaucoma was diagnosed using the International Society of Geographical and Epidemiological Ophthalmology criteria. The mean (SD) age at exam was 42.3 (16.7) years and 54.1% of the sample was female. In the total sample, the mean (SD) intraocular pressure (IOP) and vertical cup-to-disc ratio (VCDR) was 14.55 (2.42) mmHg and 0.31 (0.15), respectively. The 97.5th and 99.5th percentile for IOP and VCDR was 20 mmHg and 22 mmHg, and 0.7 and 0.8, respectively. The overall prevalence of glaucoma in the population was 2.30% (n = 47). Of these 47 individuals, 37 (78.7%) had primary open angle glaucoma, 6 (12.8%) had primary angle closure glaucoma, and 4 (8.5%) had secondary glaucoma. There was a significant (p = 5.86×10−6) increase in the prevalence of glaucoma with increasing age overall and across glaucoma subtypes. Six individuals with glaucoma (12.8%) were blind in at least one eye. Of the individuals with glaucoma, 93.6% were previously undiagnosed. In individuals aged 40 years or older (n = 1057, 51.4% female), the mean (SD) IOP and VCDR was 14.39 (2.63) mmHg and 0.34 (0.16), respectively, and glaucoma prevalence was 4.16% (n = 44). The prevalence of glaucoma and undiagnosed disease is high in the Jirel population of Nepal. This study will inform strategies to minimize glaucoma-associated burden in Nepal.